PENERAPAN KOMPRES HANGAT DALAM MENURUNKAN HIPERTERMIA PADA ANAK YANG MENGALAMI KEJANG DEMAM SEDERHANA - Nova Ari Pangesti, Bayu Seto Rindi Atmojo, Kiki A (AKPER Pemkab Purworejo, 2020)
ebrile seizures are seizures that occur due to temperature increases reaching 38ºC, because the extracranium process, usually occurs at the age of under 5 years. Simple febrile seizures are generic seizures lasting several seconds and less than 15 minutes. Objective: to analyze the temperature of participants who have hyperthermia by giving a warm compress at RSUD Dr. Tjitrowardojo Purworejo. Methods: The study used a descriptive method in the form of case studies. The subjects in this study were 2 pediatric patients and their families who experienced simple febrile seizures. Results: after giving warm compresses to participant 1 and participant 2 for 3 days showed that the temperature of participant 1 decreased from 38.5 ° C to 36.3 ° C and participant 2 also decreased from 38.2 ° C to 37.0 ° C. Conclusion: Giving warm compresses is an effective action to reduce temperature in participants who experience hyperthermia.